2017
DOI: 10.1053/j.ajkd.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Early Kidney Disease With Brain Magnetic Resonance Imaging and Cognitive Function in African Americans With Type 2 Diabetes Mellitus

Abstract: Background Relationships between early kidney disease, neurocognitive function and brain anatomy are poorly defined in African Americans with type 2 diabetes mellitus (T2DM). Study Design Cross-sectional associations were assessed between cerebral anatomy and cognitive performance with estimated glomerular filtration rate (eGFR) and urinary albumin-creatinine ratio (UACR) in African Americans with T2DM. Setting a& Participants African Americans with cognitive testing and cerebral magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 49 publications
2
21
0
1
Order By: Relevance
“…The third independent variable associated with WMH progression was GFR, with lower GFR values in WHM progressors. The finding that patients with impaired renal function have an increased WMH burden has been reported in several cross-sectional studies both in subjects with cardiovascular risk factors [35,36], and patients with previous stroke [37,38]. Nevertheless, this is the first longitudinal study in patients with a carotid plaque showing a significant association between renal impairment and risk of WMH progression.…”
Section: Discussionsupporting
confidence: 52%
“…The third independent variable associated with WMH progression was GFR, with lower GFR values in WHM progressors. The finding that patients with impaired renal function have an increased WMH burden has been reported in several cross-sectional studies both in subjects with cardiovascular risk factors [35,36], and patients with previous stroke [37,38]. Nevertheless, this is the first longitudinal study in patients with a carotid plaque showing a significant association between renal impairment and risk of WMH progression.…”
Section: Discussionsupporting
confidence: 52%
“…The prevalence of CSVD and risk factors for CSVD are significantly higher among African Americans compared to non-Hispanic Whites [2]. This disparity exists even after adjusting for traditional dementia risk factors and relevant covariates [3,4]. Several studies have reported on the contribution of genetic variation, such as the APOE ε4 genotype, to the incidence and prevalence of dementia and cognitive decline in both African Americans and non-Hispanic Whites [[5], [6], [7]].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown that African Americans with SCT have a significantly higher risk for atrial fibrillation and other cardiovascular phenotypes [11,12]. Both CKD [3,13,14] and atrial fibrillation [15,16] have been reported to be significantly associated with an increased risk of cognitive decline and dementia. A recent study also showed that young African Americans were significantly more likely to have evidence of silent cerebral infarcts on MRI compared to healthy age and sex matched controls.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far, brain imaging studies of patients with non-end-stage kidney disease are limited. Recent structural MRI studies have found abnormal brain volumes in patients with CKD ( Murea et al, 2015 ; Freedman et al, 2017 ; Hartung et al, 2018 ), but it remains unclear whether specific brain changes associated with cognitive impairment will occur in the non-end-stage of CKD.…”
Section: Introductionmentioning
confidence: 99%